DEVELOPMENT OF RICE HUSK-BASED ADSORBENTS FOR METAL FINISHING WASTEWATER TREATMENT - KHAN, TAIMUR (2016)
Heavy metals have adverse e!Tects on human health and environment. Heavy metals waste is a potential source of surface and ground water contamination if it is not properly collected, treated and disposed of. The main objective of the study was to develop rice husk-based adsorbents and to determine their etlectiveness in removing various toxic heavy metals (cadmium (Cd (II)), chromium (Cr (VI)), copper (Cu (II)), lead (Pb (II)), nickel (Ni (II)) and zinc (Zn (II)) from aqueous solution as well as from metal finishing wastewater.